Public Perception in Government Public Relations Communication in the Digital Era through Public Communication Practices A Rapid Review Approach - Joko Bramono Susilo; Nur Annafi FSM (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
In the digital era, government public communications face complex new challenges, particularly in building positive public perceptions of government performance. Digital transformation has changed patterns of interaction between the government and the public, creating an increasingly critical, connected, and participatory society. The primary issue in this research is the effectiveness of government Public Relations (PR) digital communication strategies in responding to the dynamics of this digital society. The research focuses on how innovations in government PR communication content influence public perceptions in the context of digital public communications. This research uses a Rapid Review approach, analyzing nine relevant scientific articles published in 2025 and applying the ADO(Antecedent–Decision–Outcome) framework. Three main theories serve as the basis for the analysis: Government Communication Theory, Image Management Theory, and Digital Public Participation Theory. The findings indicate that the success of government public communications in the digital era is significantly influenced by three main factors: first, innovative, creative and interactive content that attracts attention and builds engagement; second, a two-way communication strategy that adapts to public feedback; and third, consistency in shaping and maintaining a positive and credible digital narrative. Furthermore, this research reveals that participatory and open digital communication can increase public trust, reduce disinformation, and strengthen the legitimacy of government institutions. Thus, this research provides a practical contribution to the development of public communication strategies that are more participatory, inclusive, and responsive to the dynamics of the digital era. The results of this study are expected to serve as a reference for government communication practitioners in designing effective and relevant public communication policies amidst the rapid and competitive flow of information.